Development of Lumio-Based Interactive Learning Media by Smart for Taxation Elements in Class XI Accounting and Institutional Finance of State Vocational Schools in Surabaya - Fitri Mahendrastuti; Moh Danang Bahtiar (Journal of Innovative and Creativity, 2025)
The quality of education in schools, it can be focused on improving the quality of learning in the classroom. The selection of learning media must be in accordance with the Merdeka Curriculum so that learning runs properly and can improve the quality of learning. With the advancement of technology, researchers finally developed interactive learning media with the help of the Lumio by Smart Website for Taxation subjects. The purpose of this development research is to see the feasibility of the interactive learning media developed, as well as to see the response of students after using the product during the trial. This type of research is Research and Development (R&D) using the ADDIE development model which has five stages consisting of Analyze, Design, Development, Implementation, and Evaluation. The product trial was carried out at SMKN 1 Surabaya, SMKN 4 Surabaya, SMKN 6 Surabaya, and SMKN 10 Surabaya together with class XI Accounting and Institutional Finance students who had received Income Tax Article 21 material in the Taxation subject. The feasibility results based on the validation of subject matter expert obtained a score of 92%, media expert 98%, and language expert 100%, where the three percentage scores were classified as "Very Feasible". The results of the student response questionnaire obtained a score of 96% classified as "Very Good". From the two results, it means that interactive learning media based on Lumio by Smart in the Taxation subject is feasible to be used in learning.